Wider die Verunsicherung Arbeitslosenkomitees in der Schweiz, 1975-2002 - Zahn, Anina (Chronos Verlag, 2021)
1975: Switzerland is in crisis. To deal with the rising unemployment figures, compulsory unemployment insurance is introduced. At the same time, self-organised groups of unemployed people emerge, calling themselves unemployment committees. They persistently protest against deteriorations in unemployment insurance, even in the subsequent crises of the 1980s and 1990s. This book tells the story of unemployment in a decisive transitional phase of industrial society from the perspective of those affected. What does social security mean for the unemployed? For a long time, welfare state history dealt with insurance and institutional developments. This is also the case with unemployment insurance. However, a history of unemployment cannot be written without the unemployed. Their relationship to the welfare state is therefore examined using the example of five unemployment committees in German-speaking and French-speaking Switzerland up to 2002. How did they interact with the authorities? What were their protests against? Their criticism: the welfare state not only provides security, it can also make people feel insecure. To counteract this, the unemployed joined forces, seized referendums and set up counselling centres, which themselves became part of social policy.